A fatherly eye : Indian agents, government power, and Aboriginal resistance in Ontario, 1918-1939 - Brownlie, Robin, 1963- (Canadian social history series., 2003)
"This study sheds new light on a time and a place we know little about. Brownlie focuses on two Indian agencies in southern Ontario - Parry Sound and Manitowaning (on Manitoulin Island) - and the contrasting management styles of two agents, John Daly and Robert Lewis, especially during the Great Depression. In administering the lives of the Anishinabek people, the government paid inadequate attention to the protection of treaty rights and was excessively concerned with maintaining control, in part through the paternalistic provision of assistance that helped to silence critics of the system and prevent political organizing. As Brownlie concludes, the Indian Affairs system still does not work well, and has come to represent all that is most oppressive about the history of colonization in this country."--Jacket.